Factors influencing patients’ satisfaction with complete dentures: a qualitative study. - Jessica de Cassia Motta Silva; Jarbas Francisco Fernandes dos Santos; Leonardo Marchini (Brazilian Dental Science)
Objective: The treatment most used worldwide for edentulism is conventional complete dentures, and the most important factor for the success of denture treatment seems to be patient satisfaction. The present study aims to use a qualitative approach to investigate factors that were previously associated with patient satisfaction with dentures by quantitative techniques (correlational studies). Material and methods: Twenty patients (12 women and 8 men, age 59-87) participated in open and semi-structured interviews, both pre- and post-treatment. All the interviews were recorded, listened to, and transcribed verbatim, after which the content was analyzed thematically. Results: For most respondents, tooth loss represented, first of all, difficulty chewing and eating. Some patients have not accepted the loss of their teeth and felt sadness and shame. Other patients have adapted to their dentures, through acceptance. Regarding expectations, patients expressed very high expectations, especially for the stability and adjustment of dentures, and also for a better appearance. The majority of respondents showed great satisfaction with treatment outcomes; their expectations were met, and the dentures did provide functional benefits. Patients also believed that a trusting relationship between the dentist and the patient plays a fundamental role in treatment outcomes, and they reported that currently dentists are more open to dialogue with their patients. Conclusion: Confidence between the dentist and the patient plays a fundamental role in their evaluation of the treatment outcomes.